2020
DOI: 10.1200/jco.2020.38.15_suppl.5514
|View full text |Cite
|
Sign up to set email alerts
|

Overall survival (OS) results of phase III ARAMIS study of darolutamide (DARO) added to androgen deprivation therapy (ADT) for nonmetastatic castration-resistant prostate cancer (nmCRPC).

Abstract: 5514 Background: DARO is a structurally distinct androgen receptor inhibitor with a favorable safety profile, approved for treating men with nmCRPC after demonstrating significantly prolonged metastasis-free survival, compared with placebo (PBO), in the phase III ARAMIS trial: median 40.4 vs 18.4 months, respectively (HR 0.41; 95% CI 0.34–0.50; P<0.0001). We report final analyses of OS and prospectively collected, patient-relevant secondary endpoints, and updated safety results. Methods: 1509 patients (pts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 0 publications
1
26
0
3
Order By: Relevance
“…As SGARIs are emerging as new treatment options for nm-CRPC patients given their impact on improving MFS and OS, [11][12][13][14][15][16] this study provides new and timely insights on how patients and caregivers weigh the benefits and risks of these new treatments. While these new SGARIs are similar in efficacy, they have different safety profiles that may differentially impact patients' QoL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As SGARIs are emerging as new treatment options for nm-CRPC patients given their impact on improving MFS and OS, [11][12][13][14][15][16] this study provides new and timely insights on how patients and caregivers weigh the benefits and risks of these new treatments. While these new SGARIs are similar in efficacy, they have different safety profiles that may differentially impact patients' QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike first generation AR inhibitors, SGARIs demonstrated a significant clinical benefit through the prolongation of MFS and in particular OS in this patient population. [11][12][13][14][15][16] However, since this patient population is relatively asymptomatic, it is important to carefully balance risks and benefits when selecting SGARI treatments to optimize the quality of a nmCRPC patient's survival. Our results indicate that nmCRPC patients and caregivers preferred treatments with lower AE burden and were willing to forego substantial amounts of OS to reduce the risk and severity of AEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ADT in terms of statistically significant improvement in metastasis-free survival [15][16][17]. Updated data from the ARI trials also showed increase in overall survival compared with placebo (HR for apalutamide 0.78 [95% CI 0.64-0.96; P = 0.0161]) [27]; HR for darolutamide 0.69 [95% CI 0.53-0.88; P < 0.003] [28]; HR for enzalutamide 0.73 [95% CI 0.61-0.89; P = 0.001] [29].…”
Section: Aris In Nmcrpc and Effects On Bone: Insights From Clinical Tmentioning
confidence: 98%
“…In the phase-3 ARAMIS trial, 1509 patients with nmCRPC were randomized to ADT plus either darolutamide or placebo [ 31 ]. The final analysis showed a statistically significant OS benefit corresponding to a 31% reduction in the risk of death in the treatment cohort (HR 0.69, 95% CI 0.53–0.88, p = 0.003) [ 32 ]. Regarding the most common AEs of darolutamide (any grade), only fatigue (12.1% vs. 8.7%), back pain (8.8% vs. 9.0%), arthralgia (8.1% vs. 9.2%), and hypertension (6.6% vs. 5.2%) were different between the two groups.…”
Section: Main Textmentioning
confidence: 99%